Effect of fabric layer on sound absorption of micro-perforated panel - Putra, Azma; Kassim, Dg Hafizah; Ismail, Rainah; Jamil, Mohamad Hafiz; Prasetiyo, Iwan (Praise Worthy Prize, 2020)
Micro-Perforated Panel (MPP) absorber becomes an alternative to common fibrous porous absorber without owning health and environmental issues. The system is considered as the next generation of absorber in noise control. However, such a system suffers from narrow absorption bandwidth so that its application becomes limited. Theoretically, the frequency range with effective absorption is determined by the surface acoustic impedance controlled by the perforation ratio, hole diameter and cavity depth. Hence, by keeping those parameters to be constant, an intervention to the change of impedance is expected to be useful in widening the absorption bandwidth. In this research, textile materials from woven fabrics namely cotton fabric, plain fabric and satin fabric were used to cover the surface of Micro Perforated Panel (MPP) absorber either at the front or at the back surface. The sound absorption coefficients were measured for the normal incidence using an impedance tube. From the measured results, it is found that the presence of the fabric on MPP surface can improve the MPP absorber in terms of amplitude as well as the frequency bandwidth of absorption. Moreover, the placement of the woven fabric at downstream area is more beneficial than at the upstream area